Accuracy of loop-mediated isothermal amplification for the diagnosis of Clostridium difficile infection: a systematic review - Lloyd, Aaron (2015)
Loop-mediated isothermal DNA amplification (LAMP) are currently used as standalone diagnostic test for C. difficile infection (CDI). We assessed the diagnostic accuracy of LAMP for the diagnosis of CDI. We searched 5 databases to identify studies that compared LAMP with culture cytotoxicity neutralization assay or anaerobic toxigenic culture (TC) of C. difficile. We used the random-effects model to calculate pooled sensitivities, specificities, diagnostic odds ratios and their 95% confidence intervals (CIs). The search of the databases yielded 16 studies (6,979 samples) that met inclusion criteria. When TC was used as the gold standard (6,572 samples), bivariate analysis yielded a mean sensitivity of 0.95 (95%CI, 0.93-0.97; I2 = 67.4) and a mean specificity of 0.99 (95%CI, 0.96-1.00; I2 = 97.0). LAMP is a useful diagnostic tool with high sensitivity and specificity for detecting CDI. The results should however be interpreted only in the presence of clinical suspicion and symptoms of CDI.